Business Strategy of PT Soca Cipta Niaga - Risnandar, Mohammad Tedi; Larso, Dwi (The Indonesian Journal of Business Administration, 2013)
Growth of Muslim population in Indonesia goes rapidly every year, not only in Indonesia but also worldwide. The need for special Muslim socks is very high mainly to support the hajj and umroh which are performed annually. PT Soka Cipta Niaga (PT SCN), one of the manufacturers of Muslim socks, is currently emergig. "SOKA" socks products has received positive feedback from its customers. But problem arises, where consumers who use socks PT SCN do not recognize the trademark used by the company. They just have known as "wudu socks" instead of socks named "SOKA". Promotion medias used by company have no positive impact on consumer brand knowledge. To solve the problem of the company, the researcher has analyzes the customers, company, competitors, collaborators, SWOT and Porterâ€™s Five Forces. This analysis is to find out the company's strategy of â€œSokaâ€ brand. The strategy used to increase the popularity of PT SCN socks products urges its employees to actively use social media such as Twitter, Facebook and LinkedIn to introduce the company's products. Community outreach through collaboration to hold bazaar, Muslim seminars are also form of corporate promotional activities to enhance brand and product knowledge from PT SCN. In addition, an important activity is to cooperate with the organizers of hajj and umroh to provide for the needs of pilgrims socks Implementation of the strategy is based on a predetermined time. Ramadhan and hajj session is very important because the company sales will increase rapidly. The company also needs to increase the targetÂ  to be achieved in each sale periodically at particular time as a measurement of effectiveness strategies.